Preventing violence to women and children in the home: an overview. (1st March 2011) - Browne, K; Jackson, V
Abstract : It has been estimated that 4 to 16% of children are physically abused and 1 in 10 are neglected or psychologically abused, the vast majority of the time by their parents and caregivers. Disabled children are 3.8 times more likely to be physically abused than non-disabled children. The need for prevention is exemplified by a survey of young people resident in secure accommodation which shows that 4 out of 5 young offenders had adverse childhood experiences. Furthermore, it has been found that 75% of adolescents and teenagers running away from home report physical and sexual abuse as the primary reason. Hence, there is an apparent need to refocus efforts to safeguard children. This might tackle an over-reliance on social services as the lead agency for child care and protection and give more responsibility to the health sector for the prevention of child maltreatment through a public health approach, with home visitation programmes being most effective. This would provide support services to children and families in need at different stages in the child's development. Findings from a systematic review of interventions with children and their non-abusing mothers found that these interventions were effective in reducing child behaviour problems and mother's stress and PTSD symptoms. It was noted that one third of local authorities in the UK have no specialist service for dealing with domestic violence. Despite the recognition of the significant harm caused by domestic violence on children and relative risk of abuse being 23 times higher than other families, this has not led to an increase in the provision of services for children. Services for women and girls from black and ethnic minority backgrounds are even more limited. Often, both the perpetrators and the victims from all backgrounds join a waiting list for intervention and treatment concerning violence, mental health problems and therapy. Meanwhile the children remain in foster care awaiting the outcome of care proceedings with no permanent placement.